E-GOVERNANCE: A Case Study of Gyandoot Project - Mansuri, Dr. B.B. (Journal of Contemporary Research in Management (JCRM), 2013)
The Information Technology (IT) revolution in India as elsewhere has had it’s impact on the way the business of managing public services is conducted. The Governments both at the Centre and in the States including various Government agencies have realized that IT and Internet can be used in a highly effective manner to improve the Government to Citizen inter-face. This paper discusses the various developments initiatives in India in general and Gyandoot Project of Dhar district of Madhaya Pradesh in Particular.